2022
DOI: 10.1049/bme2.12063
|View full text |Cite
|
Sign up to set email alerts
|

Signal‐level fusion for indexing and retrieval of facial biometric data

Abstract: The growing scope, scale, and number of biometric deployments around the world emphasise the need for research into technologies facilitating efficient and reliable biometric identification queries. This work presents a method of indexing biometric databases, which relies on signal-level fusion of facial images (morphing) to create a multistage data structure and retrieval protocol. By successively pre-filtering the list of potential candidate identities, the proposed method makes it possible to reduce the nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Data fusion is an important and effective solution for water pollution prevention projects with a large number of samples [13][14]. Using different models such as multi-source sensors and embedded computing algorithms, it is observed that there is a certain degree of correlation between the target information and the original signal.…”
Section: Data Fusion Technologymentioning
confidence: 99%
“…Data fusion is an important and effective solution for water pollution prevention projects with a large number of samples [13][14]. Using different models such as multi-source sensors and embedded computing algorithms, it is observed that there is a certain degree of correlation between the target information and the original signal.…”
Section: Data Fusion Technologymentioning
confidence: 99%